A New Enceladus Global Control Network, Image Mosaic, and Updated Pointing Kernels From Cassini's 13‐Year Mission. Issue 10 (22nd October 2018) - Bland, M. T.; Becker, T. L.; Edmundson, K. L.; Roatsch, Th.; Archinal, B. A.; Takir, D.; Patterson, G. W.; Collins, G. C.; Schenk, P. M.; Pappalardo, R. T.; Cook, D. A.
Abstract: NASA's Cassini spacecraft spent 13 years exploring the Saturn system, including 23 targeted flybys of the small, geologically active moon Enceladus. These flybys provided a wealth of image data from Cassini's Imaging Science Subsystem. To improve the usability of the Enceladus data set, we created a new, global photogrammetric control network for Enceladus that enabled compilation of a versatile cartographic package to support geologic mapping and other investigations. The network used 586 images in four image filters with a pixel scale generally between 50 and 500 m per pixel and a phase angle less than 120° and consisted of 10, 362 tie points and 173, 704 individual image measures, averaging nearly 17 measures per tie point. Least squares bundle adjustment resulted in a root‐mean‐square residual of 0.45 pixel, corresponding to root‐mean‐square ground point uncertainties of 66, 51, and 46 m in latitude, longitude, and radius, respectively. Using our geodetic control network, we created new global image mosaics, coregistered flyby mosaics to support geologic mapping, and updated pointing kernels for every image used in the solution. These products, including the updated pointing kernels, are available to the community through NASA's Planetary Data System Imaging Annex. The bundle adjustment solution also yielded independently determined shape information, resulting in radii within the stated uncertainty of International Astronomical Union values. The challenges of the data set, and the technical methodology described here are applicable to bodies imaged during multiple flybys with variable viewing and illumination geometry, including other midsized satellites of Saturn, and the Europa Clipper mission. Plain Language Summary: In 2004, NASA's Cassini spacecraft arrived at Saturn and spent the next 13 years in orbit around the planet. During that time, cameras on Cassini took thousands of pictures of Saturn's small moon Enceladus, which has a young, fractured surface and geyser‐like plumes of ice and water vapor erupting from cracks at its south pole. The pictures provide a wealth of information but are difficult to use. Small uncertainties in the exact location and look direction of the Cassini spacecraft when the pictures were taken cause large uncertainties in locating where on the surface each picture is actually positioned. Overlapping pictures taken at different times during Cassini's mission therefore often do not properly align. We improved the usability of these pictures by identifying thousands of common points between overlapping images and mathematically performing a simultaneous realignment of more than 600 of Cassini's best pictures of Enceladus. We then combined 108 individual pictures into a single global picture that can be used for creating geologic maps. The properly aligned images and the global mosaics are available to the public via NASA's Planetary Data System Imaging Annex. Our technique is applicable to any current and future data sets acquired during multiple spacecraft encounters. Key Points: We improved the usability of Cassini image data of Enceladus by creating a global photogrammetric control network The control network enabled creation of global image mosaics and coregistered individual images to support geologic mapping Image mosaics and updated pointing kernels (image positions) are available to the community via the Planetary Data System Imaging Annex